2015
DOI: 10.12973/eurasia.2016.1399a
|View full text |Cite
|
Sign up to set email alerts
|

Student Motivation in Constructivist Learning Environment

Abstract: The purpose of this study was to investigate the relation between constructivist learning environment and students' motivation to learn science by testing whether students' selfefficacy in learning science, intrinsically and extrinsically motivated science learning increase and students' anxiety about science assessment decreases when more opportunities for personal relevance, student negotiation, shared control, critical voice, and uncertainty for scientific knowledge is provided. Constructivist Learning Envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
3
39
0
6
Order By: Relevance
“…Students are typically more motivated to engage with material that interests them or have relevance for important aspects of their lives (Cetin‐Dindar, 2016; Pintrich, 2012; Wentzel & Brophy, 2014). It is better to assign problems and tasks with relevance to their current academic lives that the students can see (Klegeris & Hurren, 2011; LaForce, Noble, & Blackwell, 2017; Pintrich & De Groot, 2003; Zhou, Kolmos, & Nielsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Students are typically more motivated to engage with material that interests them or have relevance for important aspects of their lives (Cetin‐Dindar, 2016; Pintrich, 2012; Wentzel & Brophy, 2014). It is better to assign problems and tasks with relevance to their current academic lives that the students can see (Klegeris & Hurren, 2011; LaForce, Noble, & Blackwell, 2017; Pintrich & De Groot, 2003; Zhou, Kolmos, & Nielsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of the health factors, justice and fairness, policy and regulations in the organization, supervision and monitoring, management, and salary are of greatest importance, respectively. [ 11 ] In the resent study as well, external factors were more important, and the obtained mean score for the external factors was higher than the mean score for the internal factors. Therefore, it can be concluded that paying more attention to these factors can be effective in enhancing the midwives’ motivation.…”
Section: Discussionmentioning
confidence: 95%
“…Health factors eliminate dissatisfaction in people, and motivational factors increase their work motivation. [ 11 ] It is necessary to know effective factors in the creation of job motivation in order to enhance efficiency, job satisfaction, and organizational commitment. A study by Hoseyni et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interpretasi tahap kesediaan dalam kajian ini ditentukan melalui interpretasi tahap yang diberikan oleh Jamil Ahmad (2002) seperti ditunjukkan pada Jadual 1. (Muraina, 2015;Huberman, 2009;Kasvikis, 2016;Cetin-Dindar, 2016;Nersater, 2019;Hover et al 2016;Ceceanu, 2014;Kipping, Wadhwani & Bucheli, 2013). Oleh yang demikian, pembelajaran berasaskan bahan dapat membentuk proses pembelajaran yang menarik dan bermakna dalam membina minat terhadap mata pelajaran sejarah sebagai satu disiplin ilmu dinamik dan melahirkan murid-murid yang dapat bersaing pada peringkat global (PPK, 2018; KPM, 2013).…”
Section: Metod Kajianunclassified